Mojżesz, Jozue i Amalekici. Nowe spojrzenie na Wj 17,8-16 w kontekście współczesnych badań nad powstaniem Pięcioksięgu - Janusz Lemański (Studia Koszalińsko-Kołobrzeskie, 2015)
The article tries to evaluate the contemporary proposal of reading Ex 17,8-16. The way of the presentation of a relation between Amalekites and Jhwh tells us that Amalekites are the model enemies of Israel. Moreover, the role of the rod of God, Moses, Aaron, Hur and Joshua let us think that the text had been developed when the traditions of Pentateuch and the historical books of the Old Testament were combined together.